2022
DOI: 10.1038/s41467-022-30011-5
|View full text |Cite
|
Sign up to set email alerts
|

An energizing role for motivation in information-seeking during the early phase of the COVID-19 pandemic

Abstract: The COVID-19 pandemic has highlighted the importance of understanding and managing information seeking behavior. Information-seeking in humans is often viewed as irrational rather than utility maximizing. Here, we hypothesized that this apparent disconnect between utility and information-seeking is due to a latent third variable, motivation. We quantified information-seeking, learning, and COVID-19-related concern (which we used as a proxy for motivation regarding COVID-19 and the changes in circumstance it ca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 74 publications
1
3
0
Order By: Relevance
“…Conducting research during this anxiety-provoking global event could affect results generally. However, at least two studies suggest that curiosity—even accompanied by increasing anxiety levels during the COVID-19 pandemic—had an effect on information seeking during the pandemic 35 , 36 . Online research is also less well-controlled than laboratory research.…”
Section: Discussionmentioning
confidence: 99%
“…Conducting research during this anxiety-provoking global event could affect results generally. However, at least two studies suggest that curiosity—even accompanied by increasing anxiety levels during the COVID-19 pandemic—had an effect on information seeking during the pandemic 35 , 36 . Online research is also less well-controlled than laboratory research.…”
Section: Discussionmentioning
confidence: 99%
“…A second relevant perspective is offered by the psychological science of information seeking and curiosity. Work that aims to understand the driving factors behind curiosity and information seeking has flourished in recent years (e.g., Gruber & Ranganath, 2019; Murayama et al, 2019; Sharot & Sunstein, 2020), and several studies have targeted curiosity for negative content more generally (e.g., Charpentier et al, 2018; Hsee & Ruan, 2016; Oosterwijk, 2017; Scrivner et al, 2021; see Niehoff & Oosterwijk, 2020, for an overview) and COVID-19-related information specifically (Abir et al, 2022; Eschmann et al, 2023). Finally, work from the field of empathy and emotion (e.g., Tamir, 2016; Zaki, 2014) is relevant to formulate predictions about the anticipated affective impact of engaging with negative news that portrays the suffering of other people.…”
Section: Factual Versus Personal Newsmentioning
confidence: 99%
“…Relatedly, in the field of curiosity and information seeking, it is theorized that information that people deem useful for dealing with future situations is intrinsically rewarding and may therefore evoke approach behavior (Blain & Sharot, 2021). A recent study supported this view by demonstrating that the judged personal usefulness of information predicted curiosity for COVID-19-related information (Abir et al, 2022). With regards to curiosity for negative information specifically, a recent study has suggested that a curiosity for pandemic-related horror movies may help people to prepare for bad situations (Scrivner et al, 2021).…”
Section: Distinct Motives To Engage With Negative Newsmentioning
confidence: 99%
“…In relation to the COVID-19 pandemic, Abir, et al (2022) found that motivation energises people to seek information. The authors note that, "specific motivational states are associated with domain-specific differences in personal utility and information-seeking-the directing effect that is the hallmark of goal-rational behavior.…”
Section: Motivational Theoriesmentioning
confidence: 99%